Unusual Conditions Impairing Saliva Secretion: Developmental Anomalies of Salivary Glands - Togni, Lucrezia; Mascitti, Marco; Santarelli, Andrea; Contaldo, Maria; Romano, Antonio; Serpico, Rosario; Rubini, Corrado (Frontiers in Physiology, 2019)
Salivary glands (SG) arise from ectodermal tissue between 6th-12th weeks of intrauterine life through finely regulated epithelial-mesenchymal interactions. For this reason, different types of structural congenital anomalies, ranging from asymptomatic anatomical variants to alterations associated with syndromic conditions, have been described. Notable glandular parenchyma anomalies are the SG aplasia and the ectopic SG tissue. Major SG aplasia is a developmental anomaly, leading to variable degrees of xerostomia and oral dryness. Ectopic SG tissue can occur as accessory gland tissue, salivary tissue associated with branchial cleft anomalies or true heterotopic SG tissue. Among salivary ducts anomalies, congenital atresia is a rare developmental anomaly due to duct canalization failure in oral cavity, lead to salivary retention posterior to the imperforate orifice. Accessory ducts originate from the invagination of the developing duct in two places or from the premature ventral branching of the main duct. Heterotopic ducts may arise from glandular bud positioned in an anomalous site lateral to the stomodeum or from the failure of the intraoral groove development, hindering their proximal canalization. These anomalies require multidisciplinary approach to diagnosis and treatment. While ectopic or accessory SG tissue/ducts often do not require any treatment, patients with SG aplasia could benefit from strategies for restoring SG function. This article attempts to review the literature on SG parenchyma and ducts anomalies in head and neck region providing clinicians with a comprehensive range of clinical phenotypes and possible future applications of bioengineered therapies for next-generation of regenerative medicine.